Precision Measurement of the Longitudinal Double-Spin Asymmetry for Inclusive Jet Production in Polarized Proton Collisions at √𝑠=200 GeV - STAR Collaboration (Physical Review Letters, 2015)
We report a new measurement of the midrapidity inclusive jet longitudinal double-spin asymmetry, 𝐴𝐿⁢𝐿, in polarized 𝑝⁢𝑝 collisions at center-of-mass energy √𝑠=200 GeV. The STAR data place stringent constraints on polarized parton distribution functions extracted at next-to-leading order from global analyses of inclusive deep-inelastic scattering (DIS), semi-inclusive DIS, and RHIC 𝑝⁢𝑝 data. The measured asymmetries provide evidence at the 3⁢𝜎 level for positive gluon polarization in the Bjorken-𝑥 region 𝑥>0.05.
Keywords: dept.phy